2009
DOI: 10.1007/s10439-009-9728-8
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional Pelvic Floor Muscle Strength Measurement

Abstract: Pelvic floor muscle (PFM) strength measurement provides useful information for the study of pelvic floor dysfunctions. Vaginal digital palpation, intravaginal pressure measurements, and the use of a dynamometric speculum represent currently available clinical methods for evaluating PFM strength. However, none of these methods provide a dynamic measurement of pelvic floor strength in multiple directions simultaneously. The aim of the present paper is to report the development and first measurement trial of a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 22 publications
0
34
0
5
Order By: Relevance
“…W ostatnich 20 latach wynaleziono kilka wersji dynamometrów mięśni dna miednicy [51,[56][57][58][59][60][61]. Różnią się one rozmiarami, kształtem, siłą działającego wektora (siła przednio-tylna, boczno-boczna, wielokierunkowa) lub innymi technicznymi szczegółami.…”
Section: Dynamometriaunclassified
See 1 more Smart Citation
“…W ostatnich 20 latach wynaleziono kilka wersji dynamometrów mięśni dna miednicy [51,[56][57][58][59][60][61]. Różnią się one rozmiarami, kształtem, siłą działającego wektora (siła przednio-tylna, boczno-boczna, wielokierunkowa) lub innymi technicznymi szczegółami.…”
Section: Dynamometriaunclassified
“…Niektóre wersje oferują możliwość mierzenia wielokierunkowych sił wywieranych przez mięśnie dna miednicy [59,60]. Niektóre dynamometry mogą być dostosowywane do mierzenia funkcji PFM, z uwzględnieniem różnych szerokości pochwy [57,58,62].…”
Section: Dynamometriaunclassified
“…Among clinicians, the most typical method for quantification of PF function is digital palpation because it is fast, requires no equipment, and selectively depicts PFM activity better than most available biofeedback devices (Peschers et al 2001b Several manometers van Raalte and Egorov 2015;Ribeiro et al 2016), dynamometers (Dumoulin et al 2004a;Saleme et al 2009;Chamochumbi et al 2012;Romero-Cullerés et al 2017) and EMG techniques Ptaszkowski et al 2015) have been proposed to objectively quantify PF function. However, most of these methods were developed for research purposes, in contrast to the proposed sensor, which is already commercially available and has the advantage of differentiate the effects of maximum contraction of PFMs as opposed to an increase in intra-abdominal pressure (Valsalva) along the vaginal canal (Fig.3).…”
Section: Discussionmentioning
confidence: 99%
“…Some other instruments have been proposed, but they are still under development or have not been tested across pelvic floor symptoms or treatments, with only reliability studies found in the literature so far (Saleme et al 2009;JeanMichel et al 2010;Arora et al 2015;Kruger et al 2015;Martinho et al 2015;Schell et al 2016). Therefore, in the following paragraphs, the first dynamometers, mentioned in the beginning of this sub-section, will be discussed.…”
Section: Dynamometrymentioning
confidence: 99%
See 1 more Smart Citation